Significance of Microscopic Residual Tumor in Adenocarcinoma of Stomach and Esophagogastric Junction after Gastrectomy with D2 Lymphadenectomy - Thammawat Parakonthun; Narathip Parichardsombat; Hugo Salomon; Rosero Paredes; Chainarong Phalanusittheph; Voraboot Taweerutchana; Atthaphorn Trakarnsanga; Jirawat Swangsri; Thawatchai Akaraviputh; Asada Methasate; Vitoon Chinswangwatanakul (Siriraj Medical Journal, 2018)
Objective: Microscopic residual tumor (R1 resection) may have a significant negative impact on prognosis of patients with adenocarcinoma of stomach and esophagogastric junction. Results of R1 resection on survival and recurrence patterns have not yet been thoroughly investigated in Thailand. The aim of this study was to study the oncological outcomes of R1 resection after curative intended surgery. Methods: We retrospectively analyzed the medical records of patients who underwent curative intended surgery from 2005 to 2013 at Siriraj Hospital. Results: 162 patients underwent curative intended gastrectomy with radical lymphadenectomy. 122 (75.3%) patients received R0 resection (non-residual group), 40 (24.7%) patients had microscopic residual tumor (residual group). Microscopic residual tumor was associated with tumor size (p=0.008), tumor extension (p=0.028), pT-stage (p=0.012), pN-stage (p=0.012), and AJCC/TNM stage (p<0.001). Large tumor size (≥5 cm.) and number of metastatic lymph nodes (≥3 nodes) were the factors contributing to higher rate of microscopic residual tumor on multivariate analysis (p=0.024 and 0.039, respectively). Median overall survival of non-residual and residual groups were 34.6 and 16.4 months (p=0.065). Median disease-free survival of non-residual and residual groups were 13.2 and 10.2 months (p=0.099). Distant metastasis was the most common site of recurrence in both groups. R1 resection was associated with worse 5-year survival rate (17.5% vs 34.0%, p=0.049). Conclusion: Microscopic residual tumor was associated with larger tumor size and more number of metastatic lymph nodes. R1 resection resulted in worse prognosis. Distant metastasis was the most common site of recurrence, therefore, we might suggest systemic chemotherapy as an adjuvant treatment after curative intended surgery.